Evaluasi Manajemen Sekolah Dasar Studi Kasus dalam Menantang Paradigma Konvensional dan Menciptakan Inovasi Pendidikan Berkelanjutan - Sahra, Ai Patimah; Komalasari, Kokom; Ismail Kayyis, Ika; Andrian, Muhamad; Iskandar, Sofyan (LPPM Institut Pendidikan Nusantara Global, 2025)
Facing the complexity of 21st century educational challenges, transforming primary school management is a strategic necessity to promote sustainable innovation. This study aims to evaluate managerial practices in primary schools undergoing a reform process to identify key factors that support and hinder the realization of educational innovation. This study used a qualitative approach with a case study design, involving several primary schools as research sites. Data were collected through in-depth interviews, participatory observation and institutional document analysis, then analyzed thematically with a qualitative descriptive approach. The results showed that the transformational leadership of the principal, the integration of technology in learning, and the implementation of an authentic assessment system are the main drivers of the creation of an innovative climate in the school environment. On the other hand, resistance to change, limited infrastructure and lack of continuous professional development programs are the main obstacles in the transformation process. This research emphasizes the importance of cross-stakeholder collaboration, strengthening human resource capacity, and adaptive and visionary leadership as the main foundations for successful transformative education management. The practical implications of these findings point to the need for policies that support the creation of a responsive, inclusive and future-oriented school ecosystem.